2021
DOI: 10.3389/fneur.2021.671890
|View full text |Cite
|
Sign up to set email alerts
|

Altered Relationship Between Heart Rate Variability and fMRI-Based Functional Connectivity in People With Epilepsy

Abstract: Background: Disruptions in central autonomic processes in people with epilepsy have been studied through evaluation of heart rate variability (HRV). Decreased HRV appears in epilepsy compared to healthy controls, suggesting a shift in autonomic balance toward sympathetic dominance; recent studies have associated HRV changes with seizure severity and outcome of interventions. However, the processes underlying these autonomic changes remain unclear. We examined the nature of these changes by assessing alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 92 publications
2
4
0
Order By: Relevance
“…These phenomena were consistent with our previous study using HRV as a surrogate of systemic autonomic function, in which we demonstrated parasympathetic hypofunction in RCVS patients in the acute stage with partial improvement in the remission stage 12 . Corroborated with our findings, previous studies also reported that the insular dysfunctions may result in significant change of HRV 38,39 . Insular lateralization may have differential cardiac effects, and the left insula is particularly related to parasympathetic control 40,41 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These phenomena were consistent with our previous study using HRV as a surrogate of systemic autonomic function, in which we demonstrated parasympathetic hypofunction in RCVS patients in the acute stage with partial improvement in the remission stage 12 . Corroborated with our findings, previous studies also reported that the insular dysfunctions may result in significant change of HRV 38,39 . Insular lateralization may have differential cardiac effects, and the left insula is particularly related to parasympathetic control 40,41 .…”
Section: Discussionsupporting
confidence: 93%
“…12 Corroborated with our findings, previous studies also reported that the insular dysfunctions may result in significant change of HRV. 38,39 Insular lateralization may have differential cardiac effects, and the left insula is particularly related to parasympathetic control. 40,41 Some studies have demonstrated potential connections of left insular damage to specific cardiac disorders with parasympathetic dysfunctions, including Takotsubo cardiomyopathy, 42,43 which is a cardiac disease that potentially shares characteristics with RCVS.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated heart rate but reduced functional activity in the corresponding regions in the present study is also consistent with the results of a study linking regional BOLD fluctuations to heart rate, in that a negative correlation occurred between the bilateral orbitofrontal cortex and heart rate (Kassinopoulos et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Even in the absence of overt behaviour, brain activity fluctuates in an organized fashion in the form of large-scale brain networks that resemble those observed during behavioral tasks (Biswal et al, 1995; Fox and Raichle, 2007; Gratton et al, 2018; Smith et al, 2009). Functional magnetic resonance imaging (fMRI) has been widely used for studying the resting-state activity of temporally correlated and spatially distributed brain regions, and has shown promise to uncover mechanisms underlying neurological disorders (Gratton et al, 2019; Kassinopoulos et al, 2021; Xia et al, 2018). However, the blood-oxygenated level dependent (BOLD) signal typically employed in fMRI studies is only partially attributed to neural activity.…”
Section: Introductionmentioning
confidence: 99%